Preliminary safety study of the Automated Wearable Artificial Kidney (AWAK) in Peritoneal Dialysis patients. Issue 4 (July 2022) - Htay, Htay; Gow, Sheena K; Jayaballa, Mathini; Oei, Elizabeth L; Chan, Choong-Meng; Wu, Sin-Yan; Foo, Marjorie WY
Background: Regeneration of peritoneal dialysis (PD) fluid using sorbent technology can provide flexibility and improve quality of life. This study examined the safety and efficacy of the automated wearable artificial kidney (AWAK) device in PD patients. Methods: This pilot study included prevalent PD patients from a single center in Singapore between 2016 and 2018. Participants underwent up to nine AWAK therapies over 72 h and were followed up for 1 month. Primary outcomes were serious adverse events (SAEs) and completion of nine therapies without device deficiency. Secondary outcomes were weekly peritoneal Kt/ V urea, solutes clearance and adverse events (AEs). Results: Twenty-one patients were screened and 15 were included in the study. Device alterations were required to overcome issues including flow occlusions initially, which resulted in three cohorts ( n = 2, 2 and 11 respectively). No SAEs were observed during the study and at the follow-ups. Common AEs were abdominal pain/discomfort (60%) and bloatedness (47%). The median estimated peritoneal weekly Kt/ V urea was 3.0 (interquartile range: 2.2–4.8). There were significant reductions in pre- and post-study median serum urea (20.8 vs. 14.9 mmol/L; p = 0.001), creatinine (976.0 vs. 667.5 µmol/L; p = 0.001), phosphate (1.7 vs. 1.5 mmol/L; p = 0.03), and β 2-microglobulin (29114.0 vs. 26339.0 µg/L; p = 0.048). Fluid reabsorption occurred among patients with residual kidney function. However, median body weights were not significantly different pre- and post-study (66.4 vs. 65.7 kg; p = 0.83). Conclusions: This preliminary study demonstrated that no SAEs were observed with the AWAK-PD device; however, 60% of participants developed abdominal pain/discomfort. Further device enhancements are needed to improve ultrafiltration and reduce AEs.